2018
DOI: 10.1093/mnras/sty1434
|View full text |Cite
|
Sign up to set email alerts
|

The stellar population and initial mass function of NGC 1399 with MUSE

Abstract: We present spatially resolved measurements of the stellar initial mass function (IMF) in NGC 1399, the largest elliptical galaxy in the Fornax Cluster. Using data from the Multi Unit Spectroscopic Explorer (MUSE) and updated state-of-the-art stellar population synthesis models from Conroy et al. (2018), we use full spectral fitting to measure the low-mass IMF, as well as a number of individual elemental abundances, as a function of radius in this object. We find that the IMF in NGC 1399 is heavier than the Mil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 108 publications
(145 reference statements)
5
65
0
Order By: Relevance
“…LoM-50, however, shows steeper positive radial gradients due to a deficit of α-elements in the inner regions. These results are in broad agreement with [Mg/Fe] gradients in observed galaxies which seem to vary on a case-by-case basis from either being flat (Mehlert et al 2003;Parikh et al 2018), to weakly positive (Spolaor et al 2008;Brough et al 2007), or strongly positive (as is the case for NGC 1399; Vaughan et al 2018b). The offsets between our simulations relative to Ref-50 are consistent with those for the (galaxy-wide) [Mg/Fe]−σe relation seen in Paper I, and are due to the decreased (increased) number of type II SNe resulting from a steeper (shallower) IMF slope in LoM-50 (HiM-50).…”
Section: Radial Gradients In Stellar Population Propertiessupporting
confidence: 87%
“…LoM-50, however, shows steeper positive radial gradients due to a deficit of α-elements in the inner regions. These results are in broad agreement with [Mg/Fe] gradients in observed galaxies which seem to vary on a case-by-case basis from either being flat (Mehlert et al 2003;Parikh et al 2018), to weakly positive (Spolaor et al 2008;Brough et al 2007), or strongly positive (as is the case for NGC 1399; Vaughan et al 2018b). The offsets between our simulations relative to Ref-50 are consistent with those for the (galaxy-wide) [Mg/Fe]−σe relation seen in Paper I, and are due to the decreased (increased) number of type II SNe resulting from a steeper (shallower) IMF slope in LoM-50 (HiM-50).…”
Section: Radial Gradients In Stellar Population Propertiessupporting
confidence: 87%
“…IMF variations within a single galaxy make sense under the 'two-phase' formation scenario, where the initial physical conditions at the beginning of each phase were completely different (which has recently been reproduced by simulations; e.g Barber et al 2019). Vaughan et al (2018) suggested that this change in the IMF (in that case for the giant elliptical NGC 1399) also coincided with the light profile transitioning from an 'inner' Sérsic component to a component suggested to be attributed to the 'accreted' stars (Spavone et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A number of earlier investigations have reported the presence of IMF gradients indicating dwarf-richer stellar populations towards the centers of massive ETGs (e.g. Martín-Navarro et al 2015a;La Barbera et al 2017;van Dokkum et al 2017;Vaughan et al 2018b;Sarzi et al 2018;Parikh et al 2018), with the exceptions in some other investigations (Vaughan et al 2018a;Zieleniewski et al 2015Zieleniewski et al , 2017McConnell et al 2016;Alton et al 2017).…”
Section: Radial Dependencementioning
confidence: 98%